Characterization of type 5 adenovirus fiber protein. - Dorsett, P H (1975)
Type 5 adenovirus fiber protein was purified and subjected to chemical characterization. Equilibrium sedimentation ultracentrifugation analysis indicated that the intact fiber has a molecular weight of approximately 183,000. Denaturation and chemical analyses implied that the fiber consists of three polypeptide chains, each of about 61,000 mol wt. Mapping of tryptic peptides and electrophoretic separation of the constituent chains suggested that the intact fiber consists of two identical and one unique polypeptide chains.